An evaluation of interactive computer training to teach instructors to implement discrete trials with children with autism. Issue 4 (15th August 2014) - Pollard, Joy S.; Higbee, Thomas S.; Akers, Jessica S.; Brodhead, Matthew T.
<x xml:space="preserve">Abstract</x> Discrete‐trial instruction (DTI) is a teaching strategy that is often incorporated into early intensive behavioral interventions for children with autism. Researchers have investigated time‐ and cost‐effective methods to train staff to implement DTI, including self‐instruction manuals, video modeling, and interactive computer training (ICT). ICT combines the best components of self‐instruction manuals and video models, and have the same benefits; however, there is limited research on this training method. Therefore, the purpose of this study was to investigate ICT to teach university students to implement DTI with children with autism. All participants' teaching fidelity increased during both role‐plays with an adult and instructional sessions with a child with autism. In addition, participants demonstrated an increase in teaching fidelity with untrained instructional programs. All participants were able to complete training in an average of 2 hr, and social validity ratings were high.